Analysis of Micro, Small and Medium Enterprises (MSMEs) Development - Sabila Kirani; Sinta Azhari; Syahrial Helmi Putra; Putri Mauliza (Outline Publisher, 2025)
This study examines the impact of entrepreneurial orientation on the development of Micro, Small, and Medium Enterprises (MSMEs) in Medan Sunggal, Medan. Entrepreneurial orientation, including proactivity, risk-taking, and innovation, plays a critical role in enhancing MSME performance, particularly in product development and market competitiveness. The research uses a quantitative approach, with data collected from 85 MSMEs in the region. Validity and reliability tests confirmed the accuracy and consistency of the instruments. Multiple linear regression analysis revealed a significant positive relationship between entrepreneurial orientation and MSME development, with an R² value of 0.807, indicating that 80.7% of the variance in MSME development can be explained by entrepreneurial orientation. The results suggest that fostering entrepreneurial qualities such as innovation and risk-taking can significantly boost MSME growth. This finding is consistent with previous research and underscores the importance of cultivating entrepreneurial skills among MSME owners and managers. The study recommends that local governments and business development organizations support entrepreneurial programs to enhance MSME performance. Future research could explore other factors affecting MSME success, such as access to finance, market conditions, and government policies, to gain a broader understanding of the dynamics influencing MSME development.